Analisis Pengembangan Instrumen Observasi Minat Belajar Anak Usia 5-6 Tahun - Afifah Afifah (Jurnal Kualita Pendidikan, 2021)
The main purpose of this study is to provide information related to how to develop an instrument to measure learning interest in children aged 5-6 years. The specific objectives are: 1) knowing the concept of instrument development, 2) knowing the instrument development procedure, 3) and knowing the testing method. This study uses a qualitative research type. The results of the study show that; First, the instrument plays a very important role in determining a research, as well as a tool used by researchers to collect data by measuring. Second, the instrument development procedure goes through several stages, starting from the definition development stage, giving the scale, reviewing item justification, preparing draft instruments, collecting test data, and analyzing test data. Third, the test method used to develop the instrument is factor analysis using SPSS and Microsoft excel software.